Zinc-Based Biomaterials for Regeneration and Therapy - Su, Yingchao (Trends Biotechnol, 2018)
Zinc has been described as the “calcium of the twenty-first century.” Zinc-based degradable biomaterials have recently emerged thanks to their intrinsic physiological relevance, biocompatibility, biodegradability, and pro-regeneration properties. Zinc-based biomaterials mainly include metallic zinc alloys, zinc ceramic nanomaterials, and zinc metal-organic frameworks (MOFs). Metallic zinc implants degrade at a desirable rate, matching the healing pace of local tissues, and stimulating remodeling and formation of new tissues. Zinc ceramic nanomaterials are also beneficial for tissue engineering and therapy thanks to their nanostructures and antibacterial properties. MOFs have large surface areas and are easily functionalized, making them ideal for drug delivery and cancer therapy. This review highlights recent developments in zinc-based biomaterials, discusses obstacles to overcome, and pinpoints directions for future research.